2014
DOI: 10.4209/aaqr.2013.06.0219
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of Atmospheric Aerosol Parameters over Greater Noida Using Ground Sunphotometer Observations

Abstract: Atmospheric aerosols over northern India are subject of significant temporal and spatial variability and many studies have been carried out to investigate their physico-chemical and optical properties. The present work emphasizes on examining the aerosol optical properties and types over Greater Noida, Delhi region, using ground-based sun photometer data during the period 2010-2012. The analysis reveals a relatively high mean aerosol optical depth at 500 nm (AOD 500 = 0.82 ± 0.39), associated with a moderate A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…The effects of aerosols on the climate and environment have been researched and discussed worldwide (Sharma et al, 2014;Dubovik et al, 2002;Eck et al, 2005;Wan et al, 2015). For example, Breon et al (2002) showed that aerosol optical depth (AOD) and the Ångström exponent (α) are two basic optical parameters of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of aerosols on the climate and environment have been researched and discussed worldwide (Sharma et al, 2014;Dubovik et al, 2002;Eck et al, 2005;Wan et al, 2015). For example, Breon et al (2002) showed that aerosol optical depth (AOD) and the Ångström exponent (α) are two basic optical parameters of aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive studies have been reported about aerosol optical properties and associated radiative forcing effects around the world (Dubovik et al, 2002;Eck et al, 2005;Li et al, 2007;Xia et al, 2007;Sharma et al, 2014), for example, Lyamani et al (2010) studied the physical and optical properties of aerosols over an urban location at Granada (Spain); Dani et al (2012) investigated the long-term variations of multi-spectral AOD over a tropical urban station in India. There are also many studies regarding the aerosol characteristics in China, for example, Xia et al (2006) reported the seasonal variability of aerosol optical properties over Beijing; Wang et al (2010) analyzed the optical characteristics of aerosol in Northeast China; Guo et al (2010) analyzed the spatio-temporal variation trends of satellite-based AOD in China during 1980e2008; Wang et al (2011) also investigated the seasonal variations in aerosol optical properties over different regions of China.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, along with aerosol physico-optical properties, the atmospheric chemical composition is also strongly influenced by LRT (Lelieveld et al, 2002;Pace et al, 2006). Therefore, there is an increase in the awareness of the potential of air-mass trajectories in advecting aerosols from distinct source regions and causing changes in the optical depth or composition or physical characteristics at far off locations (Tyson et al, 1996;Krishnamurti et al, 1998;Moorthy et al, 2001, Moorthy et al, 2003Kaskaoutis et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…AOD 500 nm ) and particle size (i.e. α) used by several investigators (Eck et al, 1999;Pace et al, 2006;Kaskaoutis et al, 2007Kaskaoutis et al, , 2009Kaskaoutis et al, , 2011Kalapureddy et al, 2009;Pathak et al, 2012;Sharma et. al.…”
Section: Accepted Manuscriptmentioning
confidence: 98%